Effect of alcohol prohibition on liver cirrhosis mortality rates in Canada from 1901 to 1956: A time‐series analysis. (25th May 2020) - Chrystoja, Bethany R.; Rehm, Jürgen; Crépault, Jean‐François; Shield, Kevin
Abstract: Introduction and Aims: The extent to which alcohol consumption in Canada was affected by alcohol prohibition in the early 20th century remains unclear. Since there is a dearth of data on consumption during this time, we estimated the effect of alcohol prohibition on alcohol consumption, as measured by changes in liver cirrhosis mortality rates in Canada. Design and Methods: Annual liver cirrhosis mortality data were obtained for 1901 to 1956 for the provinces of Alberta, British Columbia, Manitoba, New Brunswick, Nova Scotia, Ontario and Saskatchewan. Changes in death rates were assessed, by province, using autoregressive integrated moving average models. Results were pooled across provinces using a fixed effects meta‐analysis. A secondary fixed effects meta‐analysis was performed which only included provinces with data for before, during and after prohibition, and excluded provinces with data only beginning during prohibition. Results: Prohibition was associated with a statistically significant decrease in liver cirrhosis death rates only in Nova Scotia ( P = 0.01). Pooling of provincial results indicated that prohibition resulted in 0.39 (95% confidence interval 0.06, 0.72; P = 0.02) fewer liver cirrhosis deaths per 100 000 people. In the restricted meta‐analysis, prohibition resulted in 0.65 (95% confidence interval 0.18, 1.12; P < 0.01) fewer liver cirrhosis deaths per 100 000 people. Discussion and Conclusions: Although alcohol prohibition in Canada did not eliminate alcohol consumption, our findings suggest that prohibition was associated with reduced consumption, as evidenced by a reduction in liver cirrhosis mortality rates. Further, it's important to reflect on alcohol's history in Canada and use those policy lessons to guide the construction of effective cannabis legislation.